The role of the rule “No Ijtihad in The Presence of a Text” in preventing tampering with the text - Abdikadir, Ahmed Mahmoud; Al-Zinki, Salih Qadir Karim (Penerbit Universiti Kebangsaan Malaysia, 2023)
There were calls for absurd independent reasoning of the text that did not distinguish between its definitive and presumptive parts, violated the word's semantic boundaries, and took into consideration of the claimed interest. This research highlights the role of the rule in glorifying the definitive text, the purposes of glorifying it, its contribution to preventing tampering with it, analysing its role in controlling the movement of Ijtihad, and not resorting to it (Ijtihad) in the presence of a definitive text. The research followed the descriptive and analytical approach, and it finally concluded that this rule preserves the definitive text from being tampered with and manipulated under the pretext of ijtihad by controlling the methods of Ijtihad, distinguishing the correct ijtihad from others, and recommended conducting studies on the fundamental rules that control the methods of inference and deduction; To protect the text from frivolous attempts.